CONTINUOUS CREATION OF ENTREPRENEURIAL ORIENTATION: A REWARD AND REINFORCEMENT PERSPECTIVE - Baskaran, Shathees; Mahadi, Nomahaza; Abdul Rasid, Siti Zaleha; Mohd Zamil, Nor Aiza (Journal of Technology Management and Business, 2018)
Entrepreneurial orientation is important for organization’s sustainability. However, there are continuous debates discussing about organizational factors that activate entrepreneurial orientation among employees. Using data for three cement manufacturing companies in the southern part of Peninsular Malaysia, this study examined the influence of reward and reinforcement in creating entrepreneurial orientation among employees. A quantitative research occupying a web based online survey was adopted in the research. Three hypotheses examining the relationship between reward and reinforcement and three entrepreneurial orientation dimensions were formulated and tested in the research. With a response rate of 70.4 per cent, the statistical finding revealed that reward and reinforcement has significant relationship with only innovativeness while it has failed to provide similar evidence of significant association for risk-taking and also pro-activeness.